INSTRUMEN REBAB SEBAGAI MEDIA PENJUAL ARUM MANIS DI SURABAYA - Anbie Haldini Muhammad (Universitas Negeri Makassar, 2025)
This study examines the unique phenomenon of using the rebab as a sales tool for arum manis in Surabaya, illustrating an intriguing blend of musical traditions and modern economic activity within an urban context. Employing a qualitative approach and an ethnomusicological perspective, this study explores the transformation of rebabs’ function from a traditional musical instrument to an innovative promotional medium in street food sales. An in-depth analysis reveals the rebab's role as a symbol of cultural preservation and local identity amid urban modernization, as well as its creative adaptation for contemporary commercial purposes. This research also examines how the use of the rebab shapes the unique identity of arum manis sellers in Surabaya, creating differentiation in street food competition. Additionally, the study explores the sociocultural impacts of blending traditional and modern elements in an urban context, as well as its potential to revive interest in traditional music and preserve cultural heritage. The implications of this phenomenon for strategies to develop a creative economy based on local wisdom are also discussed, thereby providing valuable insights for policymakers and creative industry practitioners. In conclusion, this study highlights the flexibility of music in adapting to socio-economic changes while maintaining its role as a cultural messenger, providing a deep understanding of the dynamics of the interaction between tradition, innovation, and the economy in contemporary urban society.Kata Kunci: Rebab, Arum Manis, Ethnomusicology, Creative Economy, and Urban Cultural Identity